Growth and Performance of Securities Market in Nepal (Journal of Nepalese Business Studies, 2006)
Securities Board, Nepal, an apex regulator and facilitator of capital market, and Nepal Stock Exchange Ltd., only a single stock market, are the main constituents of securities market in Nepal. This paper attempts to study the growth trend and analyze the performance of Nepalese securities market. Likewise, the variables such as number of listed and traded companies and their securities, number of transactions, trading turnovers, paid up value, market capitalization and NEPSE index are analyzed for the secondary market.Journal of Nepalese Business Studies Vol.1(1) 2004 pp.85-92